Analisis Pembelajaran Berdiferensiasi Proses Kemampuan Literasi Sainstek Mahasiswa Pada Kegiatan Kurikulum Merdeka Belajar Kampus Merdeka - Reffiane, Fine; Winarto, Winarto; Santiani, Santiani (Universitas Negeri Malang, 2024)
Research focuses on student learning activities. Students' scientific and technological literacy skills are needed in the current technological era. The learning process is carried out differently to obtain different learning outcomes. Implementing activities in different ways for students is the task of lecturers to improve the quality of learning in class. The differentiation process carried out includes the processes of observing, doing, and reflecting. The research method uses qualitative analysis methods. The research subjects are education students, especially elementary school teacher education study program students who are currently pursuing a professional program. The research was conducted for 1 odd semester. Research success includes four indicators: material modification, use of technology, assignments and projects, and continuous feedback. The results obtained were (1) material modification (85% very good category), (2) use of technology (92% very good category), (3) assignments and projects (89% very good category) and continuous feedback (83% % good category). The results of achieving